DOSIS PUPUK ORGANIK DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS THAILAND - Ria Tri Wulandari; Palupi Puspitorini; Army Dita Serdani (Universitas Islam Balitar, 2021)
The purpose of the study was to look at the effect of organic fertilizers and mileage on the growth and yield of Thai shallot varieties. The study used a randomized design of split plots with various doses of chicken manure as the main plot and various distances as subplots. There are 4 types of chicken manure, namely P1 = chicken manure 1 ton / ha, P2 = chicken manure 1.5 tons / ha, P3 = chicken manure 2 tons / ha, and P4 = chicken manure 2.5 tons / ha. There are 3 types of distances, namely J1 = 20 cm x 40 cm (28 plants/plot), J2 = 20 cm x 50 cm (24 plants/plot), and J3 = 20 cm x 60 cm (20 plants/plot). The results showed the best treatment of chicken manure dose of 2.5 tons / ha and planting distance of 20 cm x 60 cm (P3J4).